2015
DOI: 10.1016/j.ijsolstr.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Hygro-elasto-plastic model for planar orthotropic material

Abstract: a b s t r a c tAn in-plane elasto-plastic material model and a hygroexpansivity-shrinkage model for paper and board are introduced in this paper. The input parameters for both models are fiber orientation anisotropy and dry solids content. These two models, based on experimental results, could be used in an analytical approach to estimate, for example, plastic strain and shrinkage in simple one-dimensional cases, but for studies of the combined and more complicated effects of hygro-elasto-plastic behavior, a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…The presented elasto-plastic model indicated that permanent waviness/fluting can be generated with elasto-plastic model simulations. Both studied cases presented in this paper, together with earlier studies at [33], proved the usefulness of the model in predicting the challenging deformation phenomena of orthotropic paper sheets.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The presented elasto-plastic model indicated that permanent waviness/fluting can be generated with elasto-plastic model simulations. Both studied cases presented in this paper, together with earlier studies at [33], proved the usefulness of the model in predicting the challenging deformation phenomena of orthotropic paper sheets.…”
Section: Discussionsupporting
confidence: 64%
“…(10), the parameters A 1 , A 2 , A 3 and n are the fitting constants, see Table 1. The hygroexpansivity model is based on the measurements and fitting procedures presented in [53] and [33]. The hygroexpansion coefficients β for every in-plane direction are defined by the equation…”
Section: Models For Materials Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the hygroexpansion is more affected by drying restraints when the solid content is high [175]. For dry solid contents from 55 to 100%, an increase in hygroexpansion from *0.04 to *0.16 for softwood freely dried pulp was reported [193].…”
Section: Density Fiber Content and Porositymentioning
confidence: 98%
“…This was stated as being due to the increased inter-fiber contact (see section ''Inter-fiber contact'') and the effects of pore volume [23,29,105,192,193]. However, the effect of the density is greater in freely dried sheets than in sheets dried under restraint [105].…”
Section: Density Fiber Content and Porositymentioning
confidence: 99%